Development of Coastal Tourism Potential Lombang Beach Based on Customer Perceived Value - Atika, Mery; Ariyani, Yan; Risqullah, Alfiyan (Universitas Trunojoyo Madura, 2024)
The potential that exists in the northern coastal area of Sumenep Regency is very diverse and abundant. In line with the sector that is being intensively developed by the Indonesian government, namely the tourism sector. Indonesia is also classified as a maritime country which certainly makes it one of the various factors why Indonesia is aggressively developing the coastal or marine tourism sector. This is inseparable from the principle of sustainable tourism development which maintains the integrity of natural, economic and social development, and ensures the maintenance of natural and cultural resources. Considering that Madura is a popular tourist island with 126 small islands and 48 inhabited islands, Sumenep Regency has the greatest potential for the development of coastal or marine tourism in Madura. The purpose of this study was to determine the development of coastal tourism in Lombang Beach based on customer perceived value in Sumenep. This research is a community mapping using qualitative methods with semi-structured interviews to obtain in-depth results in describing research results based on aspect categories. The research respondents were 24 Lombang beach tourists in Sumenep. The results of this study present a from of development that has been concluded based on costumer perceived value, where the results of respondents' submission based on aspects are described with different levels, as for things that need to be maintained, improved and developed from Lombang Beach both in terms of services, environment, and physical facilities in order to provide a positive experience to Lombang Beach tourists.Keywords: Coastal Tourism, Customer Perceived Value, Lombang Beach, Sumenep, Community Mapping